A New Thiourea Compound as Potential Ionophore for Metal Ion Sensor - Fatimatul Akma Awang Ngah; Emma Izzati Zakariah; Imran Fakhar; Nurul Izzaty Hassan; Lee Yook Heng; Bohari Yamin; Siti Aishah Hasbullah (Universitas Gadjah Mada, 2018)
A new thiourea compound, 2,2-oxybis(ethyl)-4-(1-naphthyl)-3-thiourea 3 has been synthesized and characterized by using FTIR, 1H-NMR, 13C-NMR, and MS spectroscopy. The binding properties of with various cations were also carried out using ‘naked eye’, UV-vis and 1H-NMR titration experiments. This compound exhibited effective binding for Hg2+ in the presence of other cations, such as Ag+, Ni2+, Sn2+, Zn2+, Fe2+, Cu2+, and Pb2+. Continuous variation titration experiments were conducted in order to determine the binding behavior for Hg2+. Stoichiometry of the host and guest binding interactions were also determined using continuous variation titration experiments and plotting molar-ratio curves. Pearson Product moment method was employed to calculate the correlation coefficient, and non-linear regression equation was used to calculate dissociation constant Kd. Molar-ratio and binding constant data substantiated the presence of binding sites for the compound 3.